2015
DOI: 10.1016/j.polymer.2015.05.047
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between decrosslinking of crosslinked high and low density polyethylenes via ultrasonically aided extrusion

Abstract: Please cite this article as: Huang K, Isayev AI, Comparison between decrosslinking of crosslinked high and low density polyethylenes via ultrasonically aided extrusion, Polymer (2015), AbstractAmong various polymer wastes, management of crosslinked plastics is a major environmental problem requiring a solution. Among various crosslinked plastics, recycling of crosslinked polyethylenes is of a great importance due to the presence of a three-dimensional network. To solve this problem, novel environmentally frien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 37 publications
0
9
0
Order By: Relevance
“…A cylinder temperature of 330 °C and a mold temperature of 130 °C were used for HPC composites, and a cylinder temperature of 300 °C and a mold temperature of 110 °C were used for LPC composites. [32]. Higher power consumption indicated that more energy was transmitted to polymer melt.…”
Section: Tensile Testingmentioning
confidence: 99%
“…A cylinder temperature of 330 °C and a mold temperature of 130 °C were used for HPC composites, and a cylinder temperature of 300 °C and a mold temperature of 110 °C were used for LPC composites. [32]. Higher power consumption indicated that more energy was transmitted to polymer melt.…”
Section: Tensile Testingmentioning
confidence: 99%
“…In particular, at the frequency zone lower than 0.5 Hz, value of loss tangent of CPP was almost independent on frequency. By comparison with CPP‐0, CPP‐300 possessed lower loss tangent, demonstrating the effect of the ultrasound on formation of branching and crosslinked structure .…”
Section: Resultsmentioning
confidence: 94%
“…In particular, at the frequency zone lower than 0.5 Hz, value of loss tangent of CPP was almost independent on frequency. By comparison with CPP-0, CPP-300 possessed lower loss tangent, demonstrating the effect of the ultrasound on formation of branching and cross-linked structure [49,50]. Figure 5 shows the plots of complex viscosity, which depended on the molecular weight and structure, as a function of frequency for all samples at 2008C.…”
Section: Resultsmentioning
confidence: 96%
“…[14][15][16] Efforts to handle XLLDPE waste in an environmentally responsible manner have been sparse. While earlier work focused on reducing its size for downcycling into a filler material, [15,17] more recent reports included batch pan-milling, [14,18,19] supercritical fluid-assisted reactions in batch and continuous modes, [16,20,21] and ultrasonic melt extrusion [22,23] to chemically or mechanochemically decompose the crosslinks. The development of LDPE vitrimers led to a material with reversible crosslinks.…”
Section: Introductionmentioning
confidence: 99%